1998
DOI: 10.1111/j.1600-0676.1998.tb00826.x
|View full text |Cite
|
Sign up to set email alerts
|

Stromal expression of urokinase‐type plasminogen activator receptor (uPAR) is associated with invasive growth in primary liver cancer

Abstract: Aims/Buckground: Expression of urokinase-type plasminogen activator receptor (uPAR) was studied in 25 hepatocellular carcinomas (HCCs) and seven cholangiocellular carcinomas (CCCs) by immunohistochemistry. Methods und Results: uPAR was expressed mostly by host cells distributed along the tumour-host interface in all cases of HCC and CCC, and its expression was higher in CCC. These uPAR-positive cells were identified as macrophages by observation of serial sections stained for CD68, a marker for macrophages. Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 40 publications
1
10
0
Order By: Relevance
“…Expression of uPAR in colon cancer liver metastases has not previously been reported. In hepatocellular carcinomas it has been found that uPAR mRNA and protein is expressed primarily in stromal macrophages and myofibroblasts as well as in few cancer cells 28–30…”
Section: Discussionmentioning
confidence: 83%
“…Expression of uPAR in colon cancer liver metastases has not previously been reported. In hepatocellular carcinomas it has been found that uPAR mRNA and protein is expressed primarily in stromal macrophages and myofibroblasts as well as in few cancer cells 28–30…”
Section: Discussionmentioning
confidence: 83%
“…We have previously revealed the aberrant expression of laminin γ2 chain, which is an extracellular matrix protein and considered to be processed by MMP‐2 in CC 26 . MMPs and tissue inhibitor of MMPs are expressed in tumour cells and/or tumour‐associated stroma, having the role of degrading extracellular matrix proteins and regulating invasion and metastasis in CC 27–30 . CD10 creates a microenvironment that facilitates cancer cell invasion and metastasis, as well as MMPs, due to the structural similarity of CD10 to MMPs 31,32 .…”
Section: Discussionmentioning
confidence: 99%
“…26 MMPs and tissue inhibitor of MMPs are expressed in tumour cells and ⁄ or tumour-associated stroma, having the role of degrading extracellular matrix proteins and regulating invasion and metastasis in CC. [27][28][29][30] CD10 creates a microenvironment that facilitates cancer cell invasion and metastasis, as well as MMPs, due to the structural similarity of CD10 to MMPs. 31,32 Dawson et al 16 have revealed that CD10 contributes to the synthesis and inactivation of endothelin-1, a mitogenic peptide in prostatic cancer, and have implicated CD10 as a mediator of tumour invasion via tumour-stromal interactions.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously developed and characterized novel, species specific oncolytic MVs fully retargeted against the human or murine urokinase receptor (uPAR) [17,18], a GPI-anchored cell surface receptor, which is overexpressed in tumor and particularly in stromal cells, and whose role in tumor-stromal interactions and cancer progression are well established [19][20][21][22][23][24][25]. We demonstrated that systemic 10 3 10 4 10 5 10 6 10 3 10 4 10 5 10 6 10 3 10 4 10 5 10 6 10 3 10 4 10 5 10 6 10 3 10 4 10 5 10 6 10 3 10 4 10 5 10 6 10 2 10 3 10 4 10 5 10 2 10 3 10 4 10 5 10 2 10 3 10 4 10 5 10 2 10 3 10 4 10 5 10 2 10 3 10 4 10 5 10 2 10 3 10 4 10 5 10 2 10 3 10 4 10 5 administration of species specific, human (MV-huPA) or murine (MV-muPA) uPAR retargeted MVs is safe, successfully targets tumor tissues over non-cancer tissues, and is associated with significant tumor delaying effects in primary or metastatic, xenograft, and syngeneic cancer models, respectively [18,26].…”
Section: Introductionmentioning
confidence: 99%